An Error Analysis of Using Verb Form in Writing Narrative Text at Eighth Grade of SMP N 2 Pollung - Lamria Purba; Martha Indriani Samosir; Yanti Kristina Sinaga; Bloner Sinurat; Usman Sidabutar (Sean Institute, 2022)
This research research is aimed to find out the types of error on the using verb form of simple past tense in narrative text and dominant error made by eighth grade of SMP N 2 Pollung. The method of this research was descriptive qualitative research. The data were taken from students writing test on narrative text. The writing test was used to measure each student's level of learning in writing and to find out the types of students' errors. The participants were 15 students in the eighth grade of SMP N 2 Pollung. The findings of this research indicated that there were 95 total errors that students made which were classified into four categories based on the surface strategy taxonomy. Those were error of omission with 29 errors, error of addition with 13 errors, misformation with 49 errors and misordering with 4 errors. The students made the dominant error in misformation category. It can be seen from the percentage result where misformation were 52%, then followed by error of omission with 13%, error of addition with 14% and misordering with 4%.